RELATIONSHIP OF LEARNING STRATEGIES (PROBLEM SOLVING) WITH STUDENT LEARNING OUTCOMES IN FIKIH SUBJECT IN MAN 1 PADANGSIDIMPUAN - Rina Juliana (Universitas Muhammadiyah Tapanuli Selatan, 2019)
Abstract: The problem faced by teachers in today's learning is determining the right strategy in learning. The learning strategies chosen by the teachers greatly influence student learning outcomes. Learning strategies that only attempt to spend the subject matter give less meaning to students. One strategy that can be used by teachers is problem solving learning strategies. In implementing this strategy utilizing is also very important for both teachers and students. Problem solving strategies are defined as a problem that is not routine, it is not yet known how to solve it. The problem raised in this study is whether there is a relationship between learning strategies to solve problems with student learning outcomes in the field of fiqh studies in MAN 1 Padangsidimpuan? The benefits to be achieved by researchers is for teachers to be able to apply learning strategies to problem solving in improving student learning outcomes. The purpose of this study was to determine the relationship between learning strategies to solve problems with student learning outcomes in the field of fiqh studies in MAN 1 Padangsidimpuan. To achieve these objectives this study uses a quantitative approach and the type of research is correlational. Data collection techniques through questionnaires and documentation. Validity test used Pearson product moment correlation formula, while the reliability test used alpha croanbach formula. To analyze the data used inferential descriptive method that is using simple correlation. The magnitude of the relationship of variables The magnitude of the relationship between learning strategy variables problem solving and student learning outcomes is 0.860 while the contribution of variable X1 with Y is 73.96% then the remaining 26.04% is determined by other variables. Keywords: Problem Solving Learning Strategies, Learning Outcomes